2015
DOI: 10.1161/circgenetics.115.001217
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of an Endogenous Steroidal Na Pump Inhibitor Marinobufagenin, Implicated in Human Cardiovascular Diseases, Is Initiated by CYP27A1 via Bile Acid Pathway

Abstract: Background The bioactive steroid, marinobufagenin (MBG), is an endogenous Na/K-ATPase bufadienolide inhibitor that is synthetized by adrenocortical and placental cells. MBG binding to Na/K-ATPase initiates pro-fibrotic cell signaling, and heightened MBG levels are implicated in the pathogenesis of hypertension, preeclampsia and chronic kidney disease. Steroids are derived from cholesterol through the “traditional” steroidogenesis pathway initiated by enzyme CYP11A1, and via the “acidic” bile acid pathway, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 48 publications
6
59
0
4
Order By: Relevance
“…Ammonia detoxification recently been studied by Fedorova et al [192] in adrenocortical and placental cells and found to occur from cholesterol via the acidic bile acid pathway, which is controlled by enzyme mitochondrial sterol 27-hydroxylase (CYP27A1). In macrophages the needed cholesterol trafficking from the outer to the inner mitochondrial membrane is mediated by a highly regulated multimeric protein complex.…”
Section: Resultsmentioning
confidence: 99%
“…Ammonia detoxification recently been studied by Fedorova et al [192] in adrenocortical and placental cells and found to occur from cholesterol via the acidic bile acid pathway, which is controlled by enzyme mitochondrial sterol 27-hydroxylase (CYP27A1). In macrophages the needed cholesterol trafficking from the outer to the inner mitochondrial membrane is mediated by a highly regulated multimeric protein complex.…”
Section: Resultsmentioning
confidence: 99%
“…However, the identification of specific biomarkers for the early diagnosis and prognosis of lung cancer is still required (17). The most bioactive metabolite of vitamin D, 1α,25(OH) 2 D 3 has been confirmed to contribute various non-endocrine functions in addition to maintaining calcium stability; including anti-proliferative activity, induction of cell differentiation, promotion of cell cycle stagnation and apoptosis, inhibiting cytopoiesis and regulating tumor occurrence and development (18,19). Vitamin D generates 1α,25(OH) 2 CYP27A1, CYP27B1, and CYP24A1 belong to the cytochrome P450 (CYP450) family.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has provided evidence that material with MBG properties can be detected and is related to cholesterol metabolism in adrenocortical cells. Specifically, we and others have shown that production of immunologically detected MBG is independent of cholesterol side chain cleavage, can be interrupted by blockade of de novo cholesterol synthesis, and appears to involve modification of the cholesterol side chain by a pathway known to be involved in bile acid synthesis …”
Section: Introductionmentioning
confidence: 86%
“…An important area where increased knowledge is needed is identification of genes involved in the regulation and biosynthesis of this proposed endocrine material. At present, there is evidence that the CSs that can be detected in mammals by several indirect assays (functional and immunologic) may have an endogenous origin from steroid biosynthesis and may involve modification of the cholesterol side chain by CYP27A1 . However, studies to investigate the genetic control of circulating CS have not been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation